Last but not least: PA practice in Mississippi. Issue 5 (May 2017) - Harris, Tristen A.; Butler, Kenneth R.
Abstract : ABSTRACT: This article describes the history of physician assistants (PAs) in Mississippi, the last state to pass legislation allowing for PA practice. A small group of PAs in the state began pursuing a PA practice act in the early 1990s with little political advocacy experience, and in 1994, the American Academy of PAs actively joined "The Battle for Mississippi." In April 2000, after years of PA advocacy, Mississippi passed the bill that would authorize PA practice in the state.